Acute Kidney Injury due to Russell’s Viper Envenomation: First Documented Case in Nepal - Bartaula, B.; Shah, B.; Bhurtel, N.; Sharma, S.K. (Journal of Advances in Internal Medicine, 2018)
Snake bite, is a significant public health problem and medical emergency in tropical countries including Nepal. Acute renal failure is one of the devastating complications of Russell’s viper envenoming which may cause death of patient in the absence of prompt and adequate management. Treatment with anti-venom and hemodialysis can salvage the patient. Although Russell’s viper is widely distributed in Nepal, AKI due to Russell’s viper envenoming was not reported previously from Nepal.